Men and Feminism in Nepal - Mishra, Mira (Dhaulagiri Journal of Sociology and Anthropology, 2021)
This paper narrates the experience and interpretation of feminism among 15 men students and graduates of a Gender Studies program in Nepal. It analyzes the benefits men report they have enjoyed and challenges they faced in engaging with feminism. It further discusses the strategies they employed to mitigate the challenges they faced when upscaling personal engagement in feminism. Finally, it reflects on how such engagements could be inserted into the program.